1998
DOI: 10.1021/jo9804386
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymic Production of Lactams from Aliphatic α,ω-Dinitriles

Abstract: Five- and six-membered ring lactams have been prepared by first converting an aliphatic α,ω-dinitrile to an ω-cyanocarboxylic acid ammonium salt, using a microbial cell catalyst having an aliphatic nitrilase activity (Acidovorax facilis 72W, ATCC 55746) or a combination of nitrile hydratase and amidase activities (Comamonas testosteroni 5-MGAM-4D, ATCC 55744). The ω-cyanocarboxylic acid ammonium salt was then directly converted to the corresponding lactam by hydrogenation in aqueous solution, without isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…It is interesting to note that much greater site-differentiation was achieved in enzymatic hydrolysis of α,ω-dinitriles into corresponding ω-cyanoacids [11].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that much greater site-differentiation was achieved in enzymatic hydrolysis of α,ω-dinitriles into corresponding ω-cyanoacids [11].…”
Section: Resultsmentioning
confidence: 99%
“…There was a rapid initial loss of nitrile hydratase activity after 1 h, with a subsequent slower rate of inactivation at extended heating times ( Figure 1); the amidase activity was relatively stable at this same temperature. C. testosteroni 5-MGAM-4D has previously been reported to have two nitrile hydratase activities, where one nitrile hydratase could be completely inactivated by heating a suspension of the microbial cells at 50 8C for 1 h. [22] The initial rapid loss of nitrile hydratase activity observed in the first hour of heating at 50 8C was most likely due to the inactivation of the less-thermally stable nitrile hydratase activity, and the rate of nitrile hydratase inactivation after 1 h was representative of the thermal stability of the remaining nitrile hydratase.…”
Section: Characterization Of Unimmobilized and Immobilized C Testostmentioning
confidence: 99%
“…The specific activities for Comamonas testosteroni 22 ± 1 (ATCC PTA-1853), [21] Dietzia sp. ADL1 (ATCC PTA-1854) [21] and Comamonas testosteroni 5-MGAM-4D (ATCC 55744), [21,22] initially produced in unoptimized 10-L fermentations are listed in Table 1. Nitrile hydratase and amidase specific activities were determined by measuring the change in concentration of 3-HVN and 3-HVA, respectively, over time using data collected at 3-HVN or 3-HVAm concentrations greater than ca.…”
Section: Biocatalyst Screening For 3-hydroxyalkanenitrile Hydrolysismentioning
confidence: 99%
“…In this context, DiCosimo et al have reported that aliphatic dinitriles were selectively hydrolyzed to cyanocarboxylic acids by the heat-treated resting cells of Acidovorax facilis 72W. [15] Effenberger and Osswald have demonstrated that a nitrilase from Arabidopsis thaliana catalyzed the selective hydrolysis of a,w-dinitriles to w-cyanocarboxylic acids. [11] Meth-Cohn and Wang have studied the selective hydrolysis of a variety of dinitriles using Rhodococcus sp.…”
Section: Introductionmentioning
confidence: 97%
“…Nitrilase-catalyzed hydrolysis of nitriles offers a "greener" alternative, [1] because this eco-friendly biotransformation allows the clean and mild synthesis of carboxylic acids with high yield and selectivity. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Cyanocarboxylic acids are important intermediates for a variety of applications. For example, 1-cyanocyclohexaneacetic acid is a useful precursor for the synthesis of gabapentin.…”
Section: Introductionmentioning
confidence: 99%